(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2024)
Abstract The focus of this research was to find the effectiveness and the student’s responses to the topic selection method. The researcher applied a pre-experimental design by using a one-group pre-test and post-test design. This research was conducted in class C2 at the third semester of the English Education study program Universitas Muslim Indonesia which involved 8 students as the research sample. The researcher used an oral test consisting of pre-test, treatment, and post-test and then conducted a questionnaire to measure students’ responses. The researcher conducted pre-test, treatment, post-test, and the researcher found the percentage of improvement increase was 144,4% and the student’s responses were 76% (Very High), Based on the data above showed that the majority of respondents had a positive attitude in using Topic Selection method in the third-semester English education study program at Universitas Muslim Indonesia. The conclusion of this research the Topic selection method was effective in improving students’ speaking skill.